(untitled) (World Conference on Engineering and Technological Sciences, 2026)
Oxide semiconductor thin films have become highly important functional materials in modern photonic and energy-related technologies. Materials such as ZnO, CuO, and Cu₂O possess unique optical, electrical, and structural properties that enable their application in photovoltaic systems, optoelectronic devices, photonic structures, and renewable energy technologies. The performance of these materials strongly depends on deposition technology, crystal structure, and electrophysical characteristics.